A complex of nuclear pore proteins required for pore function (The Rockefeller University Press, 1991)
A family of proteins bearing novel N-acetylglucosamine residues has previously been found to be required to form functional nuclear pores. To begin to determine which of the proteins in this family are essential for pore function, antisera were raised to each of three members of the family, p62, p58, and p54. With these antisera, it was possible to deplete nuclear reconstitution extracts of the proteins and to test the depleted nuclei for nuclear transport. In the course of the experiments, it was found that the three proteins exist as a complex; antisera to any one, while specific on a protein blot, coimmunoprecipitated all three proteins. This complex of pore proteins is stable to 2 M salt, 2 M urea, and the detergent Mega 10, indicating the presence of specific and tight protein-protein interactions. By gel filtration, the complex has a molecular mass of 550-600 kD. Nuclei containing pores depleted of the complex are found to be defective for nuclear transport; moreover, we observe a strict linear correlation between the amount of complex present in nuclei and the amount of nuclear transport of which those nuclei are capable. Thus, the p62-p58- p54 complex defines a group of proteins with strong protein-protein interactions that form a unit of pore structure essential for pore function.